Knee Joint Arthroplasty - Cho, Wooshin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book presents up-to-date knowledge on all aspects of total knee joint arthroplasty (TKA). It opens by considering indications for TKA and implant selection, covering basic science, design, and prosthetic materials. The basic and advanced operative procedures, along with theoretical background, are then described in detail for both primary and revision surgery. The operative techniques for TKA in specific and complex conditions are included. Complications of TKA and their treatment are also discussed, and clear guidance is provided on postoperative management and patient education. The author introduces his personal surgical tips and opinions on controversial issues based on his experience of TKA in some 6,000 cases. Numerous helpful illustrations and radiographs from the author$1 (Bs caseload are presented to assist readers in carrying out the described procedures.s
Chapter 1: Patient Selection -- 1. Social Conditions -- 2. Economic Conditions -- 3. Psychological Conditions -- 4. Indications -- 5. Contraindications -- Chapter 2: Implant Selection -- 1. Materials -- 2. Design -- 3. Design of each component -- 4. Surgical Instruments -- Chapter 3: Preparation for the Operation -- 1. Admission Check-up -- 2. Decision -- 3. Outcome study -- 4. Patient Education -- 5. Final check-up for the Operation -- Chapter 4: Surgical Techniques -- 1. Drape -- 2. Surgical Approach -- 3. Soft Tissue Procedure -- 4. Osteotomy and Bone Preparation -- 5. Balancing -- 6. Fixation -- 7. Closure -- 8. Miscellaneous Techniques -- Chapter 5: TKA in Specific Conditions -- 1. Bone Defects -- 2. Deformity 270 -- 3. Ankylosis -- 4. Miscellaneous Conditions and Diseases -- 5. Tumor Prosthesis -- Chapter 6: Unicompartmental Knee Arthroplasty -- 1. Unicompartmental Knee Arthroplasty (UK) -- 2. Patellofemoral Arthroplasty (PFA) -- 3. Bicompartmental Knee Arthroplasty -- Chapter 7: Postoperative Management -- 1. Postoperative Care -- 2. Education -- 3. Follow up -- Chapter 8: Complications -- 1. General Complications -- 2. Knee joint Complications -- Chapter 9: Revision Arthroplasty -- 1. Introduction -- 2. Revision for Aseptic Failure -- 3. Revision of Unicompartmental Knee Arthroplasty (UK) -- 4. Revision of Infected TKA -- Chapter 10: Optional Techniques -- 1. Computer Assisted Orthopedic Surgery (CAOS) -- 2. Minimally Invasive Surgery (MIS).
Keywords: Medicine; Orthopedics; Orthopedic surgery; Medicine & Public Health; Orthopedics; Surgical Orthopedics